Comparative proteomic analysis reveals the pathological mechanisms of overuse achilles tendinopathy and the therapeutic mechanisms of ESWT and PRP - Gongzi Zhang; Tianshu Zhao; Yangxiaoxue Liu; Jianing Xu; Wenxi Luo; Hao Liu; Bei Liu; Jingxian Hou; Jiali Zhang; Ruining Wu; Ming Zhou; Liping Huang (Tissue and Cell, 2026)

An AI-driven, de novo designed all-in-one nanoplatform for cold tumor therapy - Tian Lu; Ruining Jia; Yufei Wu; Yumeng Wang; Jiyi Zhang; Qiyu Chen; Ruonan Li; Yaonan Wang; Yuji Wang (Chemical Engineering Journal, 2026)

Population structure analysis and construction of DNA fingerprinting in eggplant (Solanum melongena L.) based on whole-genome resequencing - Ruining Lai; Chuan Zhong; Jiechun Peng; Kongxiu Su; Duoduo Xiao; Bingying Zou; Meimei Shi; Jingjing Huang; Huarong Fang; Jinling He; Xinyuan Chen; Junwei Zhang; et al. (Genetic Resources and Crop Evolution, 2026)

On-site and embodied water demand of urban residential buildings in China under the Shared Socioeconomic Pathways - Hui Li; Ruining Zhang; Xueting Peng; Yangyang Guo (Environmental Impact Assessment Review, 2026)

Hybrid vesicle-camouflaged cascade nanoreactors enable dual-targeted ferroptotic killing of intracellular MRSA and immune remodeling in pneumonia - Siyuan Yu; Yueru Pang; Ziqi Shen; Feiyang Liu; Ruixin Kang; Wei Li; Ruining Li; Lin Luo; Junyan Zhang; Qi Shen (Chemical Engineering Journal, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

How did chlorine-resistant bacteria (CRB) grow on reverse osmosis membranes and cause fouling? - Yuan Bai; Yinhu Wu; Liwei Luo; Zhuowei Zhang; Ruining Wang; Haobin Wang; Zhuo Chen; Hongying Hu (Environmental Pollution, 2026)

Hyoscyamine Ameliorates Repetitive Behavior in NLG1 and SHANK3 Deficient-Mice - Dandan Lv; Ruining Liu; Xinyu Zhang; Siqi Peng; Wei Xie; Mingdao Mu; An Liu (Neuroscience Bulletin, 2026)

Corrigendum to “Flow backward alleviated the river algal blooms” [Volume 245, 15 October 2023, 120593] - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2026)

Editor's note “Phosphorus – the main limiting factor in riverine ecosystems in China” [Sci. Total Environ. 870 (2023) 161613] - Yan Chen; Jie Chen; Rui Xia; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2026)

Event-aware SWAT+ calibration for stormflows with monthly nutrient data in the Qingjiang River Basin - Ruining Wang; Xianqi Zhang; Hongyang Zhang; Yanbin Yang; Zelin Tao (Environmental Monitoring and Assessment, 2026)

Corrigendum to “Paleoenvironments and sulfur cycle anomalies of the Junggar Basin in the Middle Permian: Paleoclimatic implications for Gondwana deglaciation” [Palaeogeography, Palaeoclimatology, Palaeoecology, volume 682, 15 January 2026, 113435] - Jingqiang Tan; Haibo Xu; Xueqi Song; Jinqi Xu; Xiongwen Lou; Wenbo Zhang; Ruining Hu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Advances in targeted nutrient delivery: materials design and mechanistic perspectives for precision nutrition - Yi Wang; Guannan Liu; Ruining Zhang; Yaqiong Wang; Pei Wang; Chong Xie; Hansong Yu; Runqiang Yang (Food Research International, 2026)

Integrated analysis of laboratory and field experiments to screen rice germplasm for submergence tolerance across various growth stages - Shengqin Liu; Hao Ai; Sumei Duan; Ruining Li; Edwin Afriyie Owusu; Liangliang Lv; Zhanglun Sun; Dachao Xu; Mengzhu Zhang; Aifeng Zhou; Wei Wang; Tingting Feng; et al. (Field Crops Research, 2026)

Paleoenvironments and sulfur cycle anomalies of the Junggar Basin in the Middle Permian: paleoclimatic implications for Gondwana deglaciation - Jingqiang Tan; Haibo Xu; Xueqi Song; Jinqi Xu; Xiongwen Lou; Wenbo Zhang; Ruining Hu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Bifunctional modulation of MrBBX19 on repressor MrNAC47 and activator MrMYB12 for UV-B-mediated quercetin enhancement in Chinese bayberry (Morella rubra) - Ruining Zhang; Qianyu Wang; Jiajia Li; Jiafei Qian; Xiangrui Cui; Yunlin Cao; Yilong Liu; Xiaoyong Zhao; Di Wu; Changjie Xu; Kunsong Chen; Xian Li (Food Chemistry, 2026)

Genesis and geological significance of pyrite in the Ordovician carbonate-evaporative strata of central Ordos Basin, China - Lianqi Jia; Biao Qin; Chenlu Ma; Ruining Zheng; Jie Zhang (Marine and Petroleum Geology, 2025)

The effect of minimum temperatures on changes in river dissolved oxygen is more pronounced in the climate transition zone - Qin Zhang; Rui Xia; Kai Zhang; Haiming Li; Yan Chen; Ruining Jia; Jinghui Dou; Lina Li; Chao Yan; Xiang Li (Journal of Environmental Management, 2025)

Citric acid modification of insoluble dietary fiber from soybean residue: Microstructural reconstruction, interfacial activity enhancement and stability by pickering emulsions - Ziyue Yu; Yuting Yang; Ying Zhang; Ruining Zhang; Bo Lyu; Sainan Wang; Wendan Jing; Hansong Yu (Food Research International, 2025)

Effects of high hydrostatic pressure on starch: multi-scale structures, interactions and applications - Yuqian Zheng; Xiaoyan Qin; Wenyan Wang; Zhilong Chen; Wenlong Xie; Jun Zhao; Ruining Zhang; Sheng Li (Food Chemistry, 2025)

Exploring the toxicological network of bleomycin-induced pulmonary fibrosis: The role of long non-coding RNAs - Bingxin Li; Hongbin Shi; Yun Ma; Ruining Zhao; Haijun Zhang (Food and Chemical Toxicology, 2025)

The associations between landscape elements and soundscape perception: A meta-analysis - Ruining Zhang; Hui Ma; Chao Wang; Yuan Zhang; Jian Kang (Landscape and Urban Planning, 2025)

Soybean insoluble Fiber-EGCG binary compounds: Enhanced stability and synergistic antioxidant activity - Yi Wang; Ruining Zhang; Shidi Men; Mingzhe Li; Guannan Liu; Xiangbo Zeng; Bo Lyu; Sainan Wang; Hansong Yu (Food Chemistry, 2025)

Design and application of a reversible anti-biofouling coating: Toward sustainable and reusable medical devices - Hongxiao Shi; Ruining Zhang; Yuqian Gu; Yiguo He; Hongli Wang; Fuhao Shen; Haitao Deng; Jing Zhang; Dianyu Wang (Chemical Engineering Journal, 2025)

Targeting thioredoxin reductase 1 by Andrographolide contributes to inducing ROS-mediated apoptosis in human NSCLC cells - Jiabing Wang; Kaiwen Jin; Nan Jin; Guran Lu; Ye Zhang; Yajie Wu; Zhiyi Zhou; Ruining Wang; Xueqiang Ma; Binhui Wang; Xi Chen (Chemico-Biological Interactions, 2025)

Mechanisms of Senegenin in Regulating Oxidative Stress and Mitochondria Damage for Neuroprotection in Insomnia: Evidence from In Vivo and In Vitro Models - Honglin Jia; Zhengting Liang; Deqi Yan; Xu Chen; Ruining Liang; Jinhong Wu; Xingping Zhang (Molecular Neurobiology, 2025)

Hydrological variability significantly influences aquatic biological integrity at the spatial scale in semi-arid watersheds - Lina Li; Rui Xia; Xinghui Xia; Ming Dou; Minhua Ling; Yan Chen; Jinghui Dou; Kai Zhang; Ruining Jia; Chao Yan (Journal of Hydrology, 2025)

β-galactanase: an effective tool for the degradation of plant β-ᴅ-galactan - Yanbo Hu; Yuzhu Shen; Yudi Song; Yue Yang; Yakun Shan; Ruining Zhang; Jun Zhao (World Journal of Microbiology and Biotechnology, 2025)

MbWRKY50 confers cold and drought tolerance through upregulating antioxidant capacity associated with ROS scavenging - Xinhui Wang; Yingnan Li; Zhuo Chen; Longfeng Li; Qiqi Li; Zihan Geng; Wanda Liu; Ruining Hou; Lihua Zhang; Deguo Han (Journal of Plant Physiology, 2025)

Polystyrene and polyethylene perturb the structure of membrane: An experimental and computational study - Ruining Guan; Qiyue Wang; Dongquan Li; Binbin Guo; Weilin Wang; Ningqi Li; Jinlong Zhang; Ruitong Cai; Zeyang Cui; Haixia Zhang; Chunyan Zhao (Environmental Pollution, 2025)

Phytochemical investigation of Jie-Geng-Tang and regulatory role in the TNF-α pathway in mitigating pulmonary fibrosis using UPLC-Q-TOF/MS - Bingxin Li; Ruining Zhao; Xiaojie Jiang; Chang Liu; Yun Ma; Haijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Long-term soy dietary fiber diet modifies the intestinal internal environment: Focus on chronic ulcerative colitis - Yi Wang; Ruining Zhang; Mingzhe Li; Jiaxin Li; Guannan Liu; Sainan Wang; Bo Lyu; Hansong Yu (Food Research International, 2025)

Augmentation of antiviral immune response induced by perturbation of CD82 under microgravity condition - Yuzhi Zhang; Sijie Wang; Jiawei Chen; Yidan Zhou; Xiaoyu Yu; Ruining Peng; Longfeng Lu; Shun Li; Zhenhao Tian; Nu Zhang; Hui Yang (Fish & Shellfish Immunology, 2025)

Effects of Glutamate on Growth Performance, Gut Digestion and Antioxidant Capacity in Juvenile Little Yellow Croaker - Ruining Liu; Yu Zhang; Xiao Liang; Bao Lou; Junquan Zhu (Fishes, 2025)
This study is to explore the alleviating effects of glutamate on intestinal damage in cultured little yellow croaker. A total of 900 juvenile fish at a weight of 30.68 ± 0.12 g were randomly separated into six groups with three replicates each, and were fed a basic diet (protein at 44.42% and lipid at 12.48%) with additional glutamate at 0.00%, 0.40%, 0.80%, 1.2%, 1.60%, and 2.00%. Each replica group consisted of 50 fish in a breeding barrel (radius 1.0 m, height 1.5 m), and the experiment lasted for 54 days. The results showed that supplementation with 0.4–1.2% glutamate significantly improved the survival rate, which increased from 75.56% to 91.11%, reduced the feed conversion rate from 1.75 to 1.57, and increased the protein efficiency ratio from 1.55 to 1.85 (p

Exploring the preventive effects of Jie Geng Tang on pulmonary fibrosis induced in vitro and in vivo: a network pharmacology approach - Bingxin Li; Xiaojie Jiang; Chang Liu; Yun Ma; Ruining Zhao; Haijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A comprehensive experimental and theoretical study of thermal response mechanisms of TKX-50 and HMX - Xuan Ren; Ruining He; Xinhui Wang; Fang Wang; Xinpeng Zhang; Dingcheng Wang; Shuyuan Liu; Henry J. Curran; Jinhu Liang; Yang Li (Fuel, 2024)

Water pollution control promotes sustainable water use in Yangtze River Economic Belt——from water footprint perspective - Ruining Jia; Zhongwen Yang; Rui Xia; Yan Chen; Lu Wang; Chen Yang; Hui Zhang; Qiang Hu; Xiang Li; Yingze Yin; Nixi Zhong; Chao Yan (Environment, Development and Sustainability, 2024)

Intertwined role of mechanism identification by DFT-XAFS and engineering considerations in the evolution of P adsorbents - Ruining Zhao; Benhang Li; Siyuan Chen; Boxuan Zhang; Jiale Chen; Jiahe Sun; Xiaodong Ma (Science of The Total Environment, 2024)

Physiological and biochemical responses of arbuscular mycorrhizal fungi in symbiosis with Juglans nigra L. seedlings to alleviate salt stress - Ao Li; Chengxu Wu; Xu Zheng; Ruining Nie; Jiali Tang; Xinying Ji; Junpei Zhang (Rhizosphere, 2024)

Natural mineral and industrial solid waste-based adsorbent for perfluorooctanoic acid and perfluorooctane sulfonate removal from surface water: Advances and prospects - Siyuan Chen; Benhang Li; Ruining Zhao; Boxuan Zhang; Yuqing Zhang; Jiale Chen; Jiahe Sun; Xiaodong Ma (Chemosphere, 2024)

The effects of interaction with audiovisual elements on perceived restoration in urban parks in freezing weather - Ruining Zhang; Ling Zhu; Xinhao Yang; Rumei Han; Yuan Zhang; Jian Kang (Urban Forestry & Urban Greening, 2024)

Cleaner reactive dyeing with the recycled dyeing wastewater - Dawu Shu; Wanxin Li; Bo Han; Fangfang An; Yan Zhang; Shaolei Cao; Ruining Liu (Journal of Environmental Chemical Engineering, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Overexpression of MrMYB12 or MrMYB12/MrF3’5’H results in flavonol-rich tomato fruit that improves resistance against Botrytis cinerea during the shelf life period - Yunlin Cao; Ruining Zhang; Ruohan Ou; Yuyang Mei; Xiangrui Cui; Tong Zhang; Xiaochun Yang; Yanna Shi; Xiaoyong Zhao; Changjie Xu; Kunsong Chen; Xian Li (Postharvest Biology and Technology, 2024)

Integrated machine learning reveals aquatic biological integrity patterns in semi-arid watersheds - Lina Li; Rui Xia; Ming Dou; Kai Zhang; Yan Chen; Ruining Jia; Xiaoxuan Li; Jinghui Dou; Xiang Li; Qiang Hu; Hui Zhang; Nixi Zhong; et al. (Journal of Environmental Management, 2024)

Flow backward alleviated the river algal blooms - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2023)

Non-steady state fluctuations in water levels exacerbate long-term and seasonal degradation of water quality in river-connected lakes - Yingze Yin; Rui Xia; Yan Chen; Ruining Jia; Nixi Zhong; Chao Yan; Qiang Hu; Xiang Li; Hui Zhang (Water Research, 2023)

How to design subsidy policies for clean energy projects? A study on “coal-to-gas” project in China - Ruining Zhang; Xianneng Ai; Hui Li (Resources Policy, 2023)

The development process of plant-based meat alternatives: Raw material formulations and processing strategies - Yi Wang; Bo Lyu; Hongling Fu; Jiaxin Li; Lei Ji; Hao Gong; Ruining Zhang; Jingsheng Liu; Hansong Yu (Food Research International, 2023)

Phosphorus – The main limiting factor in riverine ecosystems in China - Yan Chen; Jie Chen; Rui Xia; Wenpan Li; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2023)

Correction to: Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Infammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Inflammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Transcriptome analysis of oil palm pistil during pollination and fertilization to unravel the role of phytohormone biosynthesis and signaling genes - Mengdi Yang; Rajesh Yarra; Ruining Zhang; Lixia Zhou; Longfei Jin; Jerome Jeyakumar John Martin; Hongxing Cao (Functional & Integrative Genomics, 2022)

Improving sulforaphane content in transgenic broccoli plants by overexpressing MAM1, FMOGS–OX2, and Myrosinase - Haiyan Cao; Ruining Liu; Jinhua Zhang; Zhiqiang Liu; Sanhong Fan; Guangdong Yang; Zhuping Jin; Yanxi Pei (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Biological prevention and control of pitaya fruit canker disease using endophytic fungi isolated from papaya - Furun Wang; Ruining Zhang; Zhouyu Yuan; Ping Chen (Archives of Microbiology, 2021)

Molecular Cloning and Identification of the 2′–5′ Oligoadenylate Synthetase 2 Gene in Chinese Domestic Pigs Through Bioinformatics Analysis, and Determination of Its Antiviral Activity Against Porcine Reproductive and Respiratory Syndrome Virus Infection - Ruining Wang; Hongfang Ma; Yinfeng Kang; Cunfa Li; Huawei Li; Erqin Zhang; Pengchao Ji; Jian He; Mengmeng Zhao (Indian Journal of Microbiology, 2018)